Genetic Diversity and Population Structure Analysis of Cultured and Wild Populations of Labeo Rohita Using Microsatellite Markers - Dr. Kamalesh Kumar Patel (International Journal of Scientific Research in Science and Technology, 2025)
The rohu, Labeo rohita, is a major freshwater fish species of economic importance in South Asian aquaculture. However, increasing reliance on hatchery-based propagation has raised concerns over the genetic integrity of cultured stocks. This study evaluated the genetic diversity and population structure of three wild (Ganges, Yamuna, Brahmaputra) and three cultured (West Bengal, Andhra Pradesh, Punjab) populations of L. rohita using 12 polymorphic microsatellite markers. A total of 180 individuals were analyzed to compare allelic richness, heterozygosity, and genetic differentiation. Results indicated significantly higher genetic diversity in wild populations (Na = 8.5, Ho = 0.75, He = 0.80) compared to cultured populations (Na = 5.3–6.1, Ho = 0.58–0.61, He = 0.64–0.67), with the Brahmaputra population showing the greatest variability. Genetic differentiation was moderate to high (FST = 0.042–0.192), and AMOVA revealed 17.6% variation among populations. STRUCTURE analysis suggested three genetic clusters (K = 3), with clear separation between wild and hatchery stocks. Principal Coordinate Analysis and Neighbor-Joining trees supported this differentiation, indicating genetic erosion and admixture in cultured lines. These findings underscore the genetic impact of domestication and unstructured breeding practices in hatcheries. To maintain genetic health, periodic introgression of wild germplasm and scientifically managed broodstock programs are recommended. The study provides critical genetic baselines for informed breeding, conservation, and resource management of Labeo rohita.
Keywords: Labeo rohita; Microsatellite Markers; Genetic Diversity; Population Structure; Aquaculture; Conservation Genetics; FST; STRUCTURE analysis